NEW PEDAGOGICAL TECHNOLOGIES IN TEACHING SURGERY - Okhunov, A.O.; Khudaibergenova , N.Sh.; Atakov, S.S.; Kasimov , U.K.; Bobabekov, A.R.; Boboev, K.; Abdurakhmanov, F. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
General surgery is a clinical subject in the early stages of the educational process in medical schools. An important aspect of mastering the subject is to bring to students the necessary elements of the link between the theoretical base and practical skills in a relatively short time. An interactive approach to mastering any subject of the surgical field should be devoted not only to the development of manual skills, but also to communication and teamwork. This is what allows the graduate to develop not only a competent skill, but teamwork.